Intranasal mesenchymal stem cell therapy to boost myelination after encephalopathy of prematurity. Issue 3 (12th October 2020) - Vaes, Josine E. G.; van Kammen, Caren M.; Trayford, Chloe; van der Toorn, Annette; Ruhwedel, Torben; Benders, Manon J. N. L.; Dijkhuizen, Rick M.; Möbius, Wiebke; van Rijt, Sabine H.; Nijboer, Cora H.
Abstract: Encephalopathy of prematurity (EoP) is a common cause of long‐term neurodevelopmental morbidity in extreme preterm infants. Diffuse white matter injury (dWMI) is currently the most commonly observed form of EoP. Impaired maturation of oligodendrocytes (OLs) is the main underlying pathophysiological mechanism. No therapies are currently available to combat dWMI. Intranasal application of mesenchymal stem cells (MSCs) is a promising therapeutic option to boost neuroregeneration after injury. Here, we developed a double‐hit dWMI mouse model and investigated the therapeutic potential of intranasal MSC therapy. Postnatal systemic inflammation and hypoxia‐ischemia led to transient deficits in cortical myelination and OL maturation, functional deficits and neuroinflammation. Intranasal MSCs migrated dispersedly into the injured brain and potently improved myelination and functional outcome, dampened cerebral inflammationand rescued OL maturation after dWMI. Cocultures of MSCs with primary microglia or OLs show that MSCs secrete factors that directly promote OL maturation and dampen neuroinflammation. We show that MSCs adapt their secretome after ex vivo exposure to dWMI milieu and identified several factors including IGF1, EGF, LIF, and IL11 that potently boost OL maturation. Additionally, we showed that MSC‐treated dWMI brains express different levels of these beneficial secreted factors. In conclusion, the combination of postnatal systemic inflammation and hypoxia‐ischemia leads to a pattern of developmental brain abnormalities that mimics the clinical situation. Intranasal delivery of MSCs, that secrete several beneficial factors in situ, is a promising strategy to restore myelination after dWMI and subsequently improve the neurodevelopmental outcome of extreme preterm infants in the future. Main Points: Intranasal MSC therapy potently restores myelination after encephalopathy of prematurity. MSCs modify their secretome in situ to support OL maturation by upregulating valuable, beneficial growth factors and/or anti‐inflammatory cytokines.